Simplified flocculation model for inorganic and polymer flocculants - Kadooka, Hiroto; Tanaka, Takanori; Jami, Mohammed Saedi; Iwata, Masashi (2013)
Simulation of flocculation process using both inorganic and polymer flocculants is very difficult because there are many factors which influence the process. In this study, a model which enables the visual understanding of qualitative trends of the flocculation system using both inorganic and polymer flocculants is proposed. It is a simplified one dimensional model which expresses flocculation under various addition manners of the flocculant. Bridging flocculation by polymer flocculant is simplified as shown in Fig.1. Flocculation by polymer flocculant is assumed to occur when there is only one polymer flocculant between two adjacent particles as indicated by arrows in Fig.1. On the other hand, the flocculation is assumed not to occur when there are more than　one polymer flocculant between particles as indicated by a triangle in Fig.1. Flocculation by inorganic flocculant is simplified as shown in Fig.2. Flocculation occurs in one place per N spaces among particles. In this study, N = 4, i.e. flocculation by inorganic flocculant occurs where indicated by arrows in Fig.2. The model is useful to express many empirical qualitative trends of flocculation.